Makro Ekonomi dan Return Saham: Suatu Telaah Pustaka di Indonesia - Herawati, Nurul; Bandi, Bandi (Jurnal Akuntansi dan Bisnis, 2019)
This article aims to examine research related to macroeconomic variables that affect stock returns in Indonesia. The study was mapped from 25 research articles published in 20 nationally accredited scientific journals over a 18-year period. The research method used "charting the field" and "analyzing the community-citation." The field mapping results showed 4 classifications of macroeconomic variables: A. general economic conditions (economic growth, industrial production index, output, gross domestic product, and foreign exchange reserves); B. interest rates and monetary policy (interest rate, amount of money supply, government bond yield, and SBI discount rate); C. price level (inflation, world oil prices, changes in gold and silver prices); and D. international activities (exchange rate, global financial crisis, and federal fund rate). The dominating macroeconomic variables are exchange rate (76%), inflation (72%), interest rate (64%), world oil prices (20%), and money supply (16%). The results of the community mapping showed that 55% of the journals have received citations and there are 52% of the writing teams who have received citations. Artikel ini bertujuan menelaah penelitian variabel makroekonomi yang memengaruhi return saham di Indonesia. Metode penelitian menggunakan “charting the field” dan “analyzing the community—citation.” Telaah didasarkan pada 25 artikel yang terpublikasi di 20 jurnal ilmiah terakreditasi nasional selama 18 tahun. Hasil pemetaan area menunjukkan empat klasifikasi variabel makroekonomi: A. kondisi ekonomi umum (pertumbuhan ekonomi, indeks produksi industri, output, produk domestik bruto, dan cadangan devisa); B. tingkat bunga dan kebijakan moneter (suku bunga, jumlah uang beredar, yield obligasi pemerintah, dan tingkat diskonto SBI); C. tingkat harga (inflasi, harga minyak dunia, perubahan harga emas, dan perak); dan D. aktivitas internasional (nilai tukar, krisis finansial global, dan federal fund rate). Variabel makroekonomi yang mendominasi adalah exchange rate (76%), inflasi (72%), interest rate (64%), harga minyak dunia (20%), dan jumlah uang beredar (16%). Hasil pemetaan komunitas menunjukkan 55% jurnal dan 52% tim penulis artikel telah mendapatkan sitasi.